3D printing and characterization of hydroxypropyl methylcellulose and methylcellulose for biodegradable support structures. (31st May 2019) - Polamaplly, Prashant; Cheng, Yiliang; Shi, Xiaolei; Manikandan, Karthick; Zhang, Xiao; Kremer, Gül E.; Qin, Hantang
Abstract: The currently available support materials used with 3D printing technology have challenges of poor dissolvability in chemical solution and difficulty to be removed from the finished part. Current support materials are usually petroleum based which has a negative impact on the environment. The goal of the project is to identify a suitable biomaterial for support structures that will eliminate the challenges of poor dissolvability and toxic waste generated by the current material. In this study, three biodegradable cellulose derivatives of methylcellulose (MC) and hydroxypropyl methylcellulose (HPMC), with different degree of substitution of hydroxyl group were used. We investigated the effect of concentrations (8, 10, and 12% w/v) of various cellulose derivatives on the rheological properties for understanding their printability. The rheological analysis revealed that all hydrogels exhibit shear-thinning properties with relatively low yield stress. Effects of printing parameters (extrusion rate, nozzle diameter, and printing speed) were optimized to obtain the desired three-dimensional structures. The water dissolution of the MC and HPMC hydrogels allowed easy removal of the support structures from the build material. Biopolymers like MC and HPMC help in moving closer towards sustainable manufacturing. Graphical abstract: Image 1 Highlights: Biopolymers (e.g., Methylcellulose and Hydroxypropyl Methylcellulose) are potential candidates for sustainable manufacturing as the support material for 3D printing technology or bio-scaffolds for tissue engineering. The printability of biopolymers could be affected by the concentration, rheological properties, extrusion and feed rate, printing speed and nozzle diameter. The optimal concentration and material type were found to be Methylcellulose A4M 12% w/v based on the rheological and dimensional analysis. The water dissolution result showed the printed support materials could be easily removed after soaked in cold water with minimized environmental stress.